Charge Carrier Trapping during Diffusion Generally Observed for Particulate Photocatalytic Films - Katayama, Kenji; Chugenji, Tatsuya; Kawaguchi, Kei (Energies (Basel), 2021)
Photo-excited charge carriers play a vital role in photocatalysts and photovoltaics, and their dynamic processes must be understood to improve their efficiencies by controlling them. The photo-excited charge carriers in photocatalytic materials are usually trapped to the defect states in the picosecond time range and are subject to recombination to the nanosecond to microsecond order. When photo-excited charge carrier dynamics are observed via refractive index changes, especially in particulate photocatalytic materials, another response between the trapping and recombination phases is often observed. This response has always provided the gradual increase of the refractive index changes in the nanosecond order, and we propose that the shallowly trapped charge carriers could still diffuse and be trapped to other states during this process. We examined various photocatalytic materials such as TiO2, SrTiO3, hematite, BiVO4, and methylammonium lead iodide for similar rising responses. Based on our assumption of surface trapping with diffusion, the responses were fit with the theoretical model with sufficient accuracy. We propose that these slow charge trapping processes must be included to fully understand the charge carrier dynamics of particulate photocatalytic materials.